DISTRIBUTION OF TREE-OF-HEAVEN, Ailanthus altissima (Mill.) Swingle, IN WROCŁAW, LOWER SILESIA, POLAND - Przemysław Bąbelewski (Acta Scientiarum Polonorum: Hortorum Cultus, 2005)
In 1998–2001, 2025 trees-of-heaven were recorded in 647 locations in Wrocław, Lower Silesia, Poland. They grew in a variety of habitats. Most were found in lowor high-density residential areas, commercial areas, and in city’s parks. These habitats were moderately to highly transformed and classified as euhemerobic, mainly β-euhemerobic. The mean level of their hemeroby was 61. This is probably an optimum level of hemeroby for tree-of-heaven growing in the urban environment. Because the highest concentration of the locations, where tree-of-heaven grows, was found in densely developed areas of the urban thermal island, it is considered a thermophilic species adapted to urban conditions. Tree-of-heaven spreads largely spontaneously. It is a pioneer species colonising habitats unsuitable for other trees. Therefore, it is recommended for planting in urban areas, especially those situated in western Poland.